2004
DOI: 10.1016/j.ssi.2004.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on anodes for direct fuel utilization in SOFC

Abstract: This paper reviews recent work on SOFC anode fabrication at the University of Pennsylvania. In this work, anode fabrication is based on the preparation of a porous YSZ matrix, into which electronic and catalytic components are added by impregnation of the appropriate metal salts. First, the methods used to prepare porous YSZ are described, along with a description of the structures that are obtained. Next, it is demonstrated that cell performance is strongly affected by the methods used to impregnate and pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 26 publications
1
63
0
5
Order By: Relevance
“…The voltage-current curves were recorded by Scribner 890ZV at a scanning rate of 50 mV s −1 . The electrochemical impedance spectra (EIS) were obtained using a Solatron 1260 frequency response analyzer in combination with a Solartron 1287 potentiostat over the frequency range from 0.1 Hz to 10 5 Hz under open-circuit conditions. A scanning electron microscope (SEM, Zeiss) was used to observe the microstructure of the cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage-current curves were recorded by Scribner 890ZV at a scanning rate of 50 mV s −1 . The electrochemical impedance spectra (EIS) were obtained using a Solatron 1260 frequency response analyzer in combination with a Solartron 1287 potentiostat over the frequency range from 0.1 Hz to 10 5 Hz under open-circuit conditions. A scanning electron microscope (SEM, Zeiss) was used to observe the microstructure of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Experimental results have demonstrated that such anode materials are effective in inhibiting carbon deposition or sulfur poisoning. [9][10][11] So far the cell designs are exclusively electrolyte-supported when metal oxide anodes are employed. This design requires relatively thick electrolyte of 300∼500 μm to support the entire cell, leading to significant ohmic resistance.…”
mentioning
confidence: 99%
“…Several review papers [104][105][106][107][108][109][110][111] and books [112] have appeared in the last few years on alternative anode materials for SOFC. The review published by Sun and Stimming [113] gives an exhaustive overview of all the anodic compositions considered so far.…”
Section: Survey Of Anode Materials For the Direct Utilization Of Hydrmentioning
confidence: 99%
“…In previous studies we have reported on the use of wet impregnation methods for the fabrication of Cu/CeO 2 /YSZ (YSZ = yttria-stabilized zirconia) composite anodes for solid oxide fuel cells (SOFC) [1][2][3][4][5][6][7][8]. In this method of anode fabrication a highly porous YSZ anode matrix is initially prepared by sintering a green YSZ tape which contains pryolyzable pore formers such as graphite.…”
Section: Introductionmentioning
confidence: 99%